Synthesis and properties of macroporous SiC ceramics synthesized by 3D printing and chemical vapor infiltration/deposition. Issue 8 (July 2020) - Baux, A.; Goillot, A.; Jacques, S.; Heisel, C.; Rochais, D.; Charpentier, L.; David, P.; Piquero, T.; Chartier, T.; Chollon, G.
Abstract: Open porosity cellular SiC-based ceramics have a great potential for energy conversion, e.g. as solar receivers. In spite of their tolerance to damage, structural applications at high temperature remain limited due to high production costs or inappropriate properties. The objective of this work was to investigate an original route for the manufacturing of porous SiC ceramics based on 3D printing and chemical vapor infiltration/deposition (CVI/CVD). After binder jetting 3D-printing, the green α-SiC porous structures were reinforced by CVI/CVD of SiC using CH3 SiCl3 /H2 . The multiscale structure of the SiC porous specimens was carefully examined as well as the elemental and phase content at the microscale. The oxidation and thermal shock resistance of the porous SiC structures and model specimens were also studied, as well as the thermal and mechanical properties. The pure and dense CVI/CVD-SiC coating considerably improves the mechanical strength, oxidation resistance and thermal diffusivity of the material.